Combination of acute appendicitis with torsion and necrosis of epiploic appendage in the transposition of internal organs - S. R. Baymakov; U. R. Zhamilov; S. Sh. Yunusov; A. Kh. Ashirmetov (Вестник хирургии имени И.И. Грекова)
Transposition of internal organs (situs inversus viscerum) is a rare version of biologically normal anatomy, in which the main internal organs have a mirror (reverse) arrangement compared to the normal position. Diseases of epiploic appendage (torsion, inflammation, necrosis) are rare and make up 0.1-0.3 % of acute diseases of the abdominal organs. A clinical case of treating a patient with acute appendicitis in combination with torsion and necrosis of epiploic appendage in the transposition of internal organs is presented.